Treatment of petroleum based industry wastewater using electrocoagulant enhance by conventional coagulant - Henry Yong, Kim Fuong (2014)
Electrocoagulation has been recognized positively to treat the wastewater from steam cleaners, textile manufacturing, mining operations, commercial laundry, municipal sewage system plants and palm oil industrial effluents. In this technology, metal cations are released into water through dissolving metal electrodes. Simultaneously, beneficial side reactions can help in removing flocculated material from the water. In present study, three steps of treatment will be carrying out to treat the petroleum based wastewater. The treatment includes preliminary settling process, coagulation process and electrocoagulation process. Preliminary settling is a natural process where no additional of chemical coagulant or additive to the samples. The settling time is set to be 24 hours for all the suspended solids to settle down. Preliminary settling process showed a big removal efficiency in total suspended solid (TSS) of the samples. The efficiency of removal for TSS during the preliminary settling process for sample T-1630, T-2300 and PPT are 0%, 72.44% and 75.14%. However, for coagulation process, the optimum dosage of coagulant required for three different samples were determined using jar test. There was huge reduction in chemical oxygen demand (COD) concentration after the coagulation process. The removal efficiency achieved for the coagulation process is 27%, 63% and 65% for sample T-1630, T-2300 and PPT respectively. Although the removal efficiency is higher, further treatment by using electrocoagulant is required to meet the discharge limit. The optimum voltage is determined and all the samples are treated with applied voltage of 100 V. The efficiency of removal for COD achieved during the electrocoagulation process for sample T-1630, T-2300 and PPT is 99.75%, 98.74% and 99.62% respectively which meet the permissible level, and save to discharge to the environment